Critical thinking development technology in the work with gifted children. Activation of pupils' mental activity at lessons of Russian language and literature - Chernousova S. A. (Pedagogical excellence and pedagogical technologies, 2016)
this article is dedicated to the organization of the Russian language and literature lessons in high school using of methods of technology development of critical thinking. Technology methods are considered as variants of methodical work with gifted children. A number of criteria for gifted children is listed, their ability to think critically is separately discussed. The author reveals the problems of graphic records on the lessons, enlarged work with questions, presents cinquain as a form of information synthesizing and organizing, and also gives the most successful examples of cinquain of students on the theme "disyllabic size of a verse."
Keywords: синквейн; технология развития критического мышления; критическое мышление; образное мышление; critical thinking; gifted children; creative thinking; одарённые дети; познавательные потребности одарённых детей; приемы технологии развития критического мышления; уроки русского языка и литературы; развитие устной и письменной речи; графическая запись; работа с вопросами; cinquain; Critical Thinking Development Technology; educational needs of gifted children; examples of critical thinking development technology; the development of speech and writing; graphic record; working with questions; lessons of the Russian language and literature